Effects of guanidinoacetic acid(gaa) supplementation in rats with chronic renal failure(crf) - Yoshiharu Tsubakihara; Terumasa Hayashi; Tatsuya Shoji (The Korean Society of Nephrology, 2012)
GAA is the precursor of creatine(CRT), an essential in the energy metabolism of muscle and nerve tissue. GAA is mainly produced in the kidney. We reported the GAA deficiency in CRF patients. This study was designed to assess the effects of GAA supplementation(10 mg,100 mg/day orally for 4 weeks respectively) for the muscle capabilities in CRF rats prepared by 5/6 nephrectomy. Muscle power was assessed by the sliding angle of the inclined screen test, and physical strength was evaluated by the time to survive in water (forced swimming method). GAA and CRT concentrations in serum, muscle and other organs were significantly decreased in CRF rats. GAA administrations significantly increased CRT content in muscle, and improved muscle capabilities dose-dependently. muscle power physical strength sliding angle; ° swimming time; min Sham 55.2±0.9 52.0±3.8 CRF(GAA 0) 42.3±1.9* 21.9±1.2* CRF(GAA 10 mg) 47.4±1.3*$ 25.5±1.1*$ CRF(GAA 100 mg) 48.8±2.1*$ 29.0±3.3*$ *; p<0.05 vs Sham $; p<0.05 vs GAA 0In conclusion, we demonstrated a deficiency of GAA and CRT, and muscle weekness in CRF rats. However, oral GAA supplementation could recover muscle content of CRT and muscle capabilities in these rats.